Antiretroviral therapy and cardiovascular risk. (25th February 2011) - Ridha, E; Devitt, E; Boffito, M; Boag, F
Abstract : The increase in the risk of myocardial infarction can be explained by antiretroviral-induced changes in conventional cardiovascular risk factors. Individual drugs within a drug class vary in their propensity to cause metabolic disturbances, and therefore, further studies are needed to determine the contribution of each drug to cardiovascular risk. A careful stratification of the cardiovascular risk and cardiovascular monitoring of HIV-infected individuals should be performed at baseline and at regular intervals during follow-up for this chronic medical condition. Standard primary and secondary prevention measures should be instituted in accordance with British Guidelines (Heart association, National Institute for Health and Clinical Excellence, etc for lipids, smoking and hypertension) Consideration of cardiovascular risk and drug–drug interactions when prescribing is crucial in the safe and optimum management of these patients. Careful communication between all care providers will help to avoid adverse outcomes.